Influence of market orientation, learning orientation, and self entrepreneural efficacy on business performance of micro, small and medium enterprises of clothing convection in Bukittinggi City - Rifqi Dwity Satria; Abror Abror (Universitas Negeri Padang, 2022)
The point of this studys is for analyze influence of markets orientations, learning orientations, self entrepreneurship on business performances. The sample in this study is clothing convection SMEs in the city of Bukittinggi. The sampling technique in this study was non-probability sampling with a sample size of 150 respondents. The data used are primary obtained from the results of respondents` responses to the proposed statement items. The result of in studys indicates that: (1) Markets orientations a significants positife effects in busines performances. (2) Learning orientations has significant positife effects in busines performances. (3) Self-entrepreneurials efficacy has significant positife effects in business performances.